Effect of Benson Relaxation Therapy on Postoperative Pain among Patients with Fractures - Muhammad Husein Haykal; Linda; Dewi Nurhanifah; Uni Afriyanti (Papua Medicine and Health Science, 2026)
Postoperative pain is one of the most common clinical problems experienced by patients with fractures and may delay recovery. Benson Relaxation Therapy is a non-pharmacological intervention that may help reduce pain intensity. This study aimed to examine the effect of Benson Relaxation Therapy on postoperative pain among patients with fractures. A pre-experimental study with a one-group pretest–posttest design was conducted involving 34 patients with fractures recruited using accidental sampling. Pain intensity was assessed using a pain scale before and after the intervention and analyzed using the Wilcoxon Signed Rank Test. Before the intervention, most participants experienced moderate pain (91.2%), whereas after the intervention the majority reported mild pain (76.5%). The Wilcoxon Signed Rank Test demonstrated a significant difference in pain intensity before and after the intervention (p = 0.001). Benson Relaxation Therapy had a significant effect on reducing postoperative pain among patients with fractures.